2009
DOI: 10.1111/j.1469-8749.2008.03171.x
|View full text |Cite
|
Sign up to set email alerts
|

Pervasive developmental disorders in individuals with cerebral palsy

Abstract: The aim of the present study was to describe the prevalence and associated factors of pervasive developmental disorders (PDD), including autistic disorder and PDD not otherwise specified (NOS), in a clinical sample of 126 children and adolescents (75 males, 51 females; age range 4–18y, mean 8y 8mo, SD 3y 8mo) with tetraplegic, hemiplegic, diplegic, dyskinetic, or mixed types of cerebral palsy (CP); 28% could not crawl or walk even with support, 29% could move with support, and 43% walked independently. Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 30 publications
6
42
2
Order By: Relevance
“…Mean scores for peer problems however were higher in the present study compared to previous studies of children with cerebral palsy (2.7–3.0) [3, 14, 15]. Peer problems were found in nine of ten children with CP in the present study, whereas Parkes et al found peer problems in one of three children in their studies and two of five children in the Canadian study by Brossard-Racine et al Peer problems were highly prevalent across all diagnostic groups, that is, emotional disorders, conduct disorders/ODD, as well as hyperactivity disorders, and could be related symptomatically to autism spectrum disorders (ASD) which have been found to be prevalent in children with CP [23]. Similarly, ASD is often part of neurodevelopmental conditions in general with a considerable overlap of conditions as described in the ESSENCE model [8].…”
Section: Discussioncontrasting
confidence: 48%
“…Mean scores for peer problems however were higher in the present study compared to previous studies of children with cerebral palsy (2.7–3.0) [3, 14, 15]. Peer problems were found in nine of ten children with CP in the present study, whereas Parkes et al found peer problems in one of three children in their studies and two of five children in the Canadian study by Brossard-Racine et al Peer problems were highly prevalent across all diagnostic groups, that is, emotional disorders, conduct disorders/ODD, as well as hyperactivity disorders, and could be related symptomatically to autism spectrum disorders (ASD) which have been found to be prevalent in children with CP [23]. Similarly, ASD is often part of neurodevelopmental conditions in general with a considerable overlap of conditions as described in the ESSENCE model [8].…”
Section: Discussioncontrasting
confidence: 48%
“…However, given the range of types of CP, functional gross motor skills, and visual impairments among children within our sample (see Table 2), it seems likely that our sample is a representative one. Note, however, that none of the children in our sample had autism spectrum disorders based on both parent report and review of medical records; although in a larger sample it is very likely that children with CP who also have autism spectrum disorders would be represented (Kilincaslan & Mukaddes, 2008). …”
Section: Methodsmentioning
confidence: 93%
“…According to the Autism Diagnostic Interview-Revised (ADI-R) [13], 49% of children under the age of 18 with myotonic dystrophy type 1 had an ASD [14], while 15% of children aged 4–18 with cerebral palsy have been reported to meet DSM-IV criteria for an ASD [15]. …”
Section: Introductionmentioning
confidence: 99%